Rivers channelization and the (dis)continuos geomorpholofical effects on the fluvial system of the Macaé River - RJ - Gustavo Cabral; Mônica Marçal (Revista Brasileira de Geomorfologia)
Hydraulic engineering works play a critical role in altering the natural behavior of a river landscape. One of the most common interventions is channelization, which directly entails the widening and deepening of the riverbed and modifying the channel's cross-sectional geometry. In Brazil, this type of work has often been conducted in floodplain areas and urban centers to ensure basic sanitation and promote economic activities. Despite its widespread use, there is a significant gap in research focused on the effects of these works on the evolution of river environments. From a geomorphological perspective, this intervention can trigger a series of changes in the pattern of hydrosedimentological processes in the river system, not limited to the altered segments. This study discusses the impacts of river channelization on the Macaé catchment, from a geomorphological approach and the recent trajectory of channel evolution. The results suggest that the intervention has intensified upstream erosion processes, characterized by rapid vertical incision of the riverbed, increased bank erosion with terrace exposure, and migration of meanders towards the channelized areas.